Are Regional Systems Greening the Economy? the Role of Environmental Innovations and Agglomeration Forces - Davide Antonioli; Simone Borghesi; Massimiliano Mazzanti (Fondazione Eni Enrico Mattei (FEEM), 2014)
The adoption and diffusion of environmental innovations (EIs) is crucial to greening the economy and achieving win-win environmental economic gains. A large and increasing literature has focused on the levers underlying EIs that are external to the firm, such as stakeholders pressure and policy pressure. Little attention, however, has been devoted so far to the possible role of local spatial spillovers which are one of the factors affecting sector/geographical specialisations. We analyse a rich dataset that covers the innovative activities and economic performances of firms in the Emilia-Romagna region in Italy, an area rich of manufacturing districts. We analyse EIs drivers and effects on firms performances through a two-step procedure. First, we look at the relevance of spatial levers, namely whether the agglomeration of EIs induces EIs in a given firm. Second, we test whether EIs are significantly related to firms economic performances. As to the importance of spatial levers, the role of agglomeration turns out to be fairly local in nature: we find that spillovers are significantly inducing innovation within municipal boundaries. Regarding economic performances, firms' productivity is positively related to EI adoption; in particular, firms that jointly adopt EIs and organizational changes show a better economic performance.
Keywords: Q5; Q55; 330; Environmental Innovations; Firm Economic Performances; Local Spillovers; Manufacturing; Agglomeration.